Draft Annual Plan 1987-88 Government of Madhya Pradesh - Planning Commission (Planning Commission, 1987)
Annual Plan,1987-88 is another action plan aimed at furthering the broad objectives of the Seventh Plan to eliminate poverty, provide productive employment and accelerate development with equity and social justice. Constraint of financial resources notwithstanding, an earnest effort will be made in the ensuing year in the direction of better utilisation of existing resources to achieve higher productivity employment and growth.
Government of Madhya Pradesh, State Planning Board